Interplay between Extracellular Matrix and Neutrophils in Diseases - Yanyan Zhu; Yumeng Huang; Qian Ji; Shengqiao Fu; Jia Gu; Ningzheng Tai; Xu Wang (Journal of Immunology Research)
The extracellular matrix (ECM) is a highly dynamic and complex network structure, which exists in almost all tissues and is the microenvironment that cells rely on for survival. ECM interacts with cells to regulate diverse functions, including differentiation, proliferation, and migration. Neutrophils are the most abundant immune cells in circulation and play key roles in orchestrating a complex series of events during inflammation. Neutrophils can also mediate ECM remodeling by providing specific matrix-remodeling enzymes (such as neutrophil elastase and metalloproteinases), generating neutrophil extracellular traps, and releasing exosomes. In turn, ECM can remodel the inflammatory microenvironment by regulating the function of neutrophils, which drives disease progression. Both the presence of ECM and the interplay between neutrophils and their extracellular matrices are considered an important and outstanding mechanistic aspect of inflammation. In this review, the importance of ECM will be considered, together with the discussion of recent advances in understanding the underlying mechanisms of the intricate interplay between ECM and neutrophils. A better comprehension of immune cell-matrix reciprocal dependence has exciting implications for the development of new therapeutic options for neutrophil-associated infectious and inflammatory diseases.